Peningkatan Kemampuan Guru SLB dalam Melakukan Asesmen Keterampilan Berbahasa Anak Autis Melalui Workshop Berbasis Digital - Marlina, Marlina; Rahmahtrisilvia, Rahmahtrisilvia (Universitas Negeri Padang, 2021)
One of the limitations of children with autism is the limitations in speaking both expressively and receptively. As a result, there are communication problems between teachers and children with autism, children with autism, and parents and caregivers mutually. This article aims to prove the improvement of teacher skills in assessing the language skills of children with autism by special teachers through digital-based workshops. Workshop participants consisted of 25 autistic special teachers in West Sumatra. The data were collected through a questionnaire that was filled in by the participants and a skills test to perform an assessment and analyzed using quantitative descriptive. The workshop results showed that there was a significant increase in teacher skills between the pretest and posttest scores in assessing the language skills of children with digital-based autism.